2007
DOI: 10.1007/s10661-007-9973-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metals in down feathers of female common eiders and their eggs from the Aleutians: arsenic, cadmium, chromium, lead, manganese, mercury, and selenium

Abstract: Concentrations of arsenic, cadmium, chromium, lead, manganese, mercury and selenium were examined in the down feathers and eggs of female common eiders (Somateria mollissima) from Amchitka and Kiska Islands in the Aleutian Chain of Alaska to determine whether there were (1) differences between levels in feathers and eggs, (2) differences between the two islands, (3) positive correlations between metal levels in females and their eggs, and (4) whether there was more variation within or among clutches. Mean leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…N = 37 for feather and N = 41 for liver and kidney nature, with the highest values at the top of the trophic web. Feather values for As reported for several bird species were between 604 to 13 ppb d-w (Burger and Gochfeld 2009;Burger et al 2008;LounsburyBillie et al 2008). The values we found in feathers are within this range for Ornate Tinamou at all sites, except for P1, with more than 2,200 ppb dw; and except for Darwin's Nothura at P2, with values higher than 1,000 ppb d-w.…”
Section: Arsenicmentioning
confidence: 98%
See 1 more Smart Citation
“…N = 37 for feather and N = 41 for liver and kidney nature, with the highest values at the top of the trophic web. Feather values for As reported for several bird species were between 604 to 13 ppb d-w (Burger and Gochfeld 2009;Burger et al 2008;LounsburyBillie et al 2008). The values we found in feathers are within this range for Ornate Tinamou at all sites, except for P1, with more than 2,200 ppb dw; and except for Darwin's Nothura at P2, with values higher than 1,000 ppb d-w.…”
Section: Arsenicmentioning
confidence: 98%
“…The body burden proportion found in feathers is relatively constant for each metal, and a high proportion of the body burden of certain metals is stored in the feathers due to their affinity to the sulfhydryl-rich keratin protein and melanin pigments (Burger et al 2008;Burger and Gochfeld 2009). Use of feathers is also interesting because of the advances in analytical chemistry, which lets us use museum specimens or other ornithological pieces to generate historical or background data, if in the past they had been obtained from currently polluted sites (Lounsbury-Billie et al 2008).…”
Section: Antimonymentioning
confidence: 99%
“…Although high concentrations of As is toxic, this element is an essential micronutrient for many species (Kabata-Pendias, 2001;Koller, 1980). Comparison of the conclusions of Burger et al (2008) and Zhang et al (2006), indicate that As concentration in the feather of the Red-Crowned Crane in Zhalong wetland were significantly lower than those in the Common Eider in Aleutian Island and Amchitak and Kiska areas and Little Egrets in Pearl Delta in southern China (p < 0.05). In addition, the daily intake (2.39 ug kg ¡1 to 2.68 ug kg ¡1 ) of the Red-Crowned Crane was significantly lower than the toxic level, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research have shown that the body burdens of metals in animals are proportional to the metal content in the environment (Mart ınez- Villegas et al, 2004;Burger et al, 2008;Fisk et al, 2005). Frequently, environmentally sensitive aquatic plants (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Army Corps of Engineers, Port Authority of New York and New Jersey, 2009). Bird eggs are collected for human food extensively in some parts of the world and are sometimes collected by recent immigrants in the New York/New Jersey harbor estuary who may have collected them in their home countries (Burger et al, 2008, Burger, personal communication, 1980).…”
mentioning
confidence: 99%